Magnetotellurics applied to the study of the Guaraní aquifer in Entre Ríos Province, N-E Argentina - Favetto, Alicia Beatriz (2011)
The South American Guaraní Aquifer System covers the entire Parana basin and part of the Chaco-Parana basin. This system is one of the most important groundwater reservoirs; it is shared by four neighboring countries covering an area larger than one million square kilometers. The geological units closely related to the Guaraní Aquifer are the Piramboia and Botucatu Formations that consist of Triassic–Jurassic aeolian, fluvial and lacustrine sandstones, and the Serra Geral basalts with clastic intercalations. Serra Geral, an effusive Cretaceous complex, covers the sandstones and provides a high degree of confinement to the system. This paper presents the interpretation of magnetotelluric (MT) data collected during 2007–2008 in Entre Ríos Province, Argentina. These data, recorded in three profiles, mainly provide the depth to the crystalline basement, determinant for the presence of aquifer-related sediments. Models showed that the discrimination of the basalts strongly depends on local electrical characteristics. Model information is quite consistent with the information from oil and thermal wells located close to the profiles.